Comparative study of two methods (hexane extraction and NMR) for the determination of oil content in an individual olive fruit. Issue 9 (5th July 2013) - Deblangey, Adeline; Roger, Jean‐Michel; Palagos, Bernard; Grenier, Gilbert; Bendoula, Ryad
<x xml:space="preserve">Abstract</x> The performance of NMR spectroscopy and hexane:isopropanol extraction (HIE) for the determination of oil content in individual olive fruit has been investigated. Both analytical methods, which are based on conventional protocols, have been adapted for samples consisting of unground pulp shreds obtained from a single olive fruit. NMR offers better precision than HIE. The latter generates more result errors during two critical steps of the protocol: weighing and lipid phase recovery. Significant differences were observed between both methods when applied on the same samples. A bias and a slope factor were highlighted and these resulted from extraction efficiency issues related to the specific structure of the sample. HIE gives results that are closer to the reference method (i.e. Soxhlet extraction) than NMR. Thus, (i) the determination of oil content in a single olive is feasible; (ii) given that NMR is faster, requires less sample handling and is less sensitive to the structure of samples, it was considered as the most suitable of the two techniques for routine measurements of oil content in individual olive fruit. Practical applications: This work is part of a research on a subject concerning olive growing. Its aim is the development of a new non‐destructive near IR (NIR) device in order to measure olive oil content directly on the tree and on individual fruits. Therefore, the results of this work suggest a reliable method to determine the oil content in a single olive to calibrate new NIR devices. The non‐destructive and rapid determination of oil content in a single olive offers several opportunities: the identification of variability within a single tree and the classification of fruits in accordance with their individual qualities.